القيادة الإدارية ودورها في عملية اتخاذ القرار - خاوة، منية (جامعة الوادي university of Eloued, 2019)
الملخص: تمثل الإدارة جميع النشاطات الإنسانية لتحقيق أهداف و غايات الفرد و المنظمات ،ولكي تحقق النجاح المرجو ،عليها تكوين كوادرها الإدارية فإذا نجحت في تكوينها وتطويرها لتلك الكوادر فإنها بذلك حققت نجاحا كبير في عملية القيادة الإدارية وكذلك تسيير شؤون الفرد و المؤسسة معا، وذلك يكون من خلال ادراكهم التام لمستوى القرارات الإدارية التي تتخذها عن طريق اتباع نمط قيادي معين. ومن خلال دراستنا التي تمحورت حول أيُّ الأنماط القيادية لها دور في عملية اتخاذ القرار وجدنا بأن أحسن و أجدر نمط قيادي هو النمط الديمقراطي لأنه يجعل من أفراد المنظمة يشعرون بالأمن والإستقرار وتحقيق الذات ،و بالتالي نجعل المؤسسة تصل إلى أبعد الحدود الممكنة في تحقيق النجاحات . وانطلاقا من ذلك طرحنا التساؤل الرئيسي التالي: هل للأنماط القيادة الإدارية دور في عملية اتخاذ القرار في المؤسسة؟. وترتب عن التساؤل الرئيسي ثلاث فرضيات فرعيه: 1- للنمط القيادي الديمقراطي دور في عملية اتخاذ القرار في المؤسسة. 2- للنمط القيادي التسلطي دور في عملية اتخاذ القرار في المؤسسة. 3- للنمط القيادي التسيبي دور في عملية اتخاذ القرار في المؤسسة. والمنهج المستخدم في هذه الدراسة هو المنهج الوصفي الذي يعد من أكثر المناهج استخداما في ميدان العلوم الاجتماعية لما يتميز به من خصوصيات تتلائم وطبيعة الظاهرة الاجتماعية من تحليل و تفسير. وتعتبر عملية اختيار عينة الدراسة من أهم الخطوات المنهجية التي يقوم عليها البحث الاجتماعي وفي هذه الدراسة تم اختيار العينة العرضية (الصدفة) بحيث تعتبر من العينات الغير احتمالية غير العشوائية بحيث لا يكون هناك تحديد مسبق لمن تشملهم العينه وتم استخدام الاستمارة كأداة من أدوات جمع البيانات ومن الآساليب الإحصائية التي تم استخدامها المتوسط الحسابي و الإنحراف المعياري و النسب المئوية. والنتائج المتوصل اليها كالتالي: 1)- النمط القيادي المتبع من طرف القائد للمؤسسة هو النمط الديمقراطي. 2)- لم تتحقق الفرضية القائلة أن النمط القيادي التسلطي دور في عملية اتخاد القرار. 3)- لم تتحقق الفرضية القائلة أن النمط القيادي التسيبي دور في عملية اتخاد القرار. 4)- اشراك العاملين في عملية اتخاد القرار تجعل من المنظمة تخرج من ظلمة الركود والانفتاح على نوافذ التقدم والتكنولوجيا. 5)- أنجع أسلوب يجعل القادة يتبعونه هو أسلوب الدبلوماسي الذي يؤكد عليه الكثير من الباحثين والذي يجمع بين الأنماط القيادية السابقة النمط الديمقراطي والنمط الديكتاتوري و النمط التسيبي. Résumé :فرنسية أو انجلزية Abstract: The administration represents all human activities to achieve the goals and objectives of the individual and organizations .in order to achieve the desired success thy must form their administrative cadres .if they succeed in their formation and development of thecadres then they achieve great success in the administrative management process on the one hand managing the affairs of the individual and the institution together .to the level of administrative de cessions that you take by following a particular leader ship style and through our study .which focused on which lea a role in the de decision –making process. we found that the best and most worthy pattern of lead leadership is the democratic because it makes the members of the organization feel safe and stable tend self –realization and the make up the foundation far as possible in achieving successes. From this we have raised the main question do you have leadership style? There main hypotheses from the question: 1-the democratic leadership style plays a role in the decision-making process Of the organization . 2-the authortarian leadership style plays a role in the decision-making process. 3-for the placental leadership pattern role in the decision-making process. The methodology used in this study is the description approach which is one of the most widely used methods in the field of social scienes because of the peculiarities that characterize the nature and social phenomenan of analys is and inter pretation. The process selecting the sample of the study is one of the study is one of the most important methodological steps on which social research is based in the studybthecrandon sample was chosen. So that it is considered a non –randon sampling so that there is no used as a data collection tool statistical methods used arithmetic mean stadard deviation percentage. . The results are as follows: 1-the leadership style adopted by the leadership of the institution is the democratic patters 2-the hypothesis that the placental leadership model has not played a role in the decision –making process has not been realised. 3-the hypothesis that the placental leader ship model is not a role in the decision –making process is not realzed . 4-involvement in the decision –making process makes the organization emerge its oppression of progress and technology 5-the most efficient style of leadership is followed by a diplomatic style that is emphasized by many resarchers and which combienes all the pre vious leading style the pseudo style.
دراسة ميدانية عمى عينة من موظفي مؤسسة بمدية جامعة – ولاية الوادي
مذكرة ماستر في علم الإجتماع تخصص تنظيم وعمل
Keywords: القيادة الإدارية، إتخاذ القرار